Long Non-coding RNA SNHG12 Functions as a Competing Endogenous RNA to Regulate MDM4 Expression by Sponging miR-129-5p in Clear Cell Renal Cell Carcinoma - Wu, Zhipeng; Chen, Dongming; Wang, Kai; Cao, Changchun; Xu, Xianlin (Frontiers in Oncology, 2019)
Clear cell renal cell carcinoma (ccRCC), the most common histological subtype of kidney cancer, shows poor prognosis and non-sensitivity to radiotherapy or chemotherapy. The lncRNA small nucleolar RNA host gene 12 (SNHG12) has been revealed to play a carcinogenic role in various neoplasms, but the underlying mechanism in ccRCC is still unclear. To explore the potential role of SNHG12 in ccRCC, the data downloaded from the Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) Data Portal was used to compare the expression of SNHG12 in tumors and adjacent normal tissues. MRNA microarray and quantitative real-time PCR revealed that SNHG12 was overexpressed in the ccRCC tissues and cell lines. Functional inhibition of SNHG12 suppressed the viability and mobility of ccRCC cells. Mechanistically, dual luciferase assay and RNA immunoprecipitation (RIP) assay showed that miR-129-5p could bind to SNHG12 directly. There was a negative relationship between SNHG12 and miR-129-5p. What’s more, we used bioinformatics-based prediction software to predict the target genes of miR-129-5p. Through data analysis and experimental verification, we found MDM4, a regulatory factor in p53 pathway, was involved in this ceRNA network. Our findings demonstrated that SNHG12 served as a sponge for miR-129-5p to regulate the expression of MDM4 and p53 pathway in the development of ccRCC.